Analisis Bentuk Perlindungan Hukum Bagi Pekerja dan Buruh Terhadap Kasus Eksploitasi Waktu Kerja Berdasarkan Undang-Undang Ketenagakerjaan - Syalsabila, Khairunisa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Work time exploitation is a serious issue faced by workers in various work environments. Factors contributing to this exploitation include low educational backgrounds, inhumane work time arrangements, ineffective government oversight, financial and resource limitations, corporate policy constraints, and profit-driven corporate interests. The government has taken steps through Labor Law No. 13 of 2003 on Manpower to protect the rights of workers, including working hours, overtime, and wages. This law provides a framework to ensure that workers experiencing work time exploitation receive adequate compensation and legal protection. Thus, legal protection for workers affected by work time exploitation is crucial in ensuring their well-being in the workplace. Further action from the government, companies, and society as a whole is necessary to address the issue of work time exploitation and create a fair and sustainable work environment for all workers.